Prize women - Lea, Caroline (New York, NY : Harper Perennial, 2023)
Toronto, 1926. Knowing that he will die without an heir, childless millionaire Charles Millar leaves behind a controversial will: the recipient of his fortune will be decided in a contest that will become a media sensation and be known as the Great Stork Derby. His money will go to the winner: the woman who bears the most children in the ten years after his death. It is a bequest that will have dramatic consequences for the lives of two women-allies and close friends. Lily di Marco is young, pregnant, and terrified of her alcoholic, violent husband. When her town is damaged by an earthquake, she flees to Toronto, arriving, by chance, on the doorstep of the glamourous Mae Thebault. While Mae presents an elegant, confident face to the world, she secretly struggles with her own tortured past and a present consumed with the never-ending burdens of motherhood. Lily enters her life at a breaking point, and soon a fierce friendship blossoms between the women. That is until the Great Depression and the contest, with its alluring prize, threatens to tear their friendship-and their lives-apart. provided by the publisher
Keywords: Inheritance and succession -- Fiction; Millionaires -- Fiction; Motherhood -- Fiction; Toronto (Ont.) -- Fiction; Historical fiction; Novels